What Is the ENSO Climatology Tool? - Caroline Staub; Clyde W. Fraisse; Eduardo Gelcer; Daniel R. Dourte (EDIS)
On a global scale, periodic anomalies in sea surface temperatures coupled with shifts in atmospheric pressure and winds, such as those associated with the El Niño Southern Oscillation (ENSO), can have profound impacts on weather conditions. ENSO affects atmospheric circulation patterns well into the midlatitudes and is the leading driver of seasonal climate variability in the United States. Tremendous advances have been made in predicting the occurrence of ENSO events with confidence three to six months in advance. This 5-page fact sheet discusses the ENSO climatology tool as well as possible challenges. Written by Caroline Staub, Clyde Fraisse, Eduardo Gelcer, and Daniel Dourte, and published by the UF Department of Agricultural and Biological Engineering, March 2017.